Resilience level among adolescent children: a school-based study in Kolkata, India - Banerjee, Rajarshi; Dasgupta, Aparajita; Burman, Jayeeta; Paul, Bobby; Bandyopadhyay, Leena; Suman, Sweta (International Journal of Contemporary Pediatrics, 2018)
Background: The rat race of modern life is affecting each and every strata of our society and adolescents are not exempted from this underlying stress. Lack of resilience in adolescents may lead to psychosocial maladaptation and psychopathology in adulthood. This study was undertaken to determine the resilience level and its possible predictors among adolescents of a Kolkata based school. Methods: This was an institution-based, observational cross-sectional study done from June-August’17 among 151 students of 7th-9th standards in a school of Kolkata. A pre-designed, pretested, structured, self-administered questionnaire along with CYRM-12 (‘Child and Youth Resilience Measure-12’) questionnaire was used. The scoring of each question was from 1-3 (higher score indicates more resilience) in CYRM-12 and in this study median attained score of 31 was taken as cut off for determining resilience level. Ethical issues were addressed. SPSS (v.16.0) was used for data analysis. Results: Among 151 students of 12-14 years, 57(37.7%) students were resilient and factors like ‘class’ [OR=4.01(1.85-8.67)]; ‘family type’ [OR=7.73(3.66-16.30)]; ‘time spent with father’ [OR=8.64(4.07-18.37)]; ‘time spent with mother’ [OR=5.97 (2.87-12.42); ‘physical activities’ [OR=9.11 (4.07-20.37) and self-rated school performance [OR=3.12(1.39-6.96)] were associated with high resilience during univariate logistic regression analysis. In the final model of multivariable logistic regression analysis by LR forward method factors like ‘family type’ [AOR=4.45(1.73-11.45)]; ‘time spent with father’ [AOR=5.27(2.04-13.6)]; ‘time spent with mother’ [AOR=4.83(1.80-12.90)] and ‘physical activities’ [AOR=8.14(2.95-22.47)] retained its significance. Conclusions: Quality parental time for children and engagement in physical activity will help to increase resilience level and build up the coping capacity.